Chemical Modelling : Applications and Theory : Vol. - 7 - Springborg, Michael; Royal Society of Chemistry (Great Britain) Staff (Cambridge : Royal Society of Chemistry, The LaVergne : Ingram Publisher Services [Distributor], 2010)
Annotation Chemical Modelling: Applications and Theory comprises critical literature reviews of all aspects of molecular modelling. Molecular modelling in this context refers to modelliing the structure, properties and reactions of atoms, molecules and materials. Each chapter provides a selective review of recent literature, incorporating sufficient historical perspective for the non-specialist to gain an understanding. With chemical modelling covering such a wide range of subjects, this Specialist Periodical Report serves as the first port of call to any chemist, biochemist, materials scientist or molecular physicist needing to acquaint themselves with major developments in the area.
Includes Index.